Safety of the rVSV ZEBOV vaccine against Ebola Zaire among frontline workers in Guinea - Juan-Giner, Aitana; Tchaton, Marie; Jemmy, Jean-Paul; Soumah, Aboubacar; Boum, Yap; Faga, Elisabetta Maria; Cisse, Mohamed; Grais, Rebecca F. (Vaccine, 2019)
As part of the ring vaccination trial in Guinea, Front Line Workers were invited to participate in a sub-study to provide additional information on the immunogenicity and safety of rVSVΔG/ZEBOV-GP. Here we summarize the information on the safety follow-up. An open-label, non-randomized, immunogenicity evaluation of one dose of rVSVΔG/ZEBOV-GP was conducted in Conakry, Guinea between March 2015 and July 2016. Front-line workers refusing vaccination were invited to participate as a control group. Participants were followed for 3 months with a subset followed-up for 6 months after vaccination. Women becoming pregnant during the follow-up were followed until pregnancy outcome. Solicited and unsolicited adverse events were monitored at each contact with participants using standardized study forms. 2016 vaccinated participants and 99 controls were included in the safety cohort. On the 3 days post-vaccination visit adverse events were very common, with over 70% of participants reporting at least one adverse event. The most frequently reported symptoms were headache, fatigue, arthralgia, subjective fever and myalgia. Among participants that completed fever diaries (n = 887), post-vaccination fever was reported by 15.22%. Comparing to the unvaccinated group, local reaction, fatigue, headache, arthralgia, myalgia and subjective fever occurring within the first 3 days post-vaccination were statistically significantly different in the vaccinated group compared to the unvaccinated. A total of 8 Serious Adverse Events were identified during follow-up. 2 SAEs were related to pregnancy. Results confirm that adverse events 3 days after vaccination with the rVSV candidate vaccine are common. The occurrence of fever is of particular concern in the context of ongoing Ebola transmission. Additional studies should address important data gaps regarding the use of the vaccine in pregnancy and other vulnerable populations.